A systematic review of advances in preparation, structures, bioactivities, structural-property relationships, and applications of Polyporus umbellatus polysaccharides - Wei Gao; Yongbin Xu; Weihao Chen; Jianjun Wu; Yu He (Food Chemistry: X)
Polyporus umbellatus (Pers.) Fries is an edible fungus species belonging to the Polygonaceae family. Polysaccharides, the predominant bioactive compounds in P. umbellatus, have been widely used due to its abundant nutritional and medicinal benefits. Since the first unrefined P. umbellatus polysaccharides (PUPs) was obtained in 1973, they have been studied for half a century, and are currently gaining increasing attention. These research findings are however quite fragmented. In this review, current relevant research data regarding techniques for the preparation (extraction, fractionation, and purification) and structural characterization (molecular weight, monosaccharide composition, glycosidic bond types, and structural features) of PUPs covering a period of over 50 years are reviewed. Furthermore, this review comprehensively examines the functional properties, structure-activity relationships, and current applications of PUPs. Future research should prioritize standardized preparation process, reliable quality control and specific mechanisms to further advance the utilization and development of PUPs and their related products.